Multifrequency computational optimization of robot path planning algorithms - Tenreiro Machado, J. A. (2019)
The computational burden of robot trajectory planning algorithms may be significant, namely when the inverse kinematics is required. Nevertheless, the variables involved have distinct bandwidths. Therefore, they have different effects upon the final result and we can adopt a multifrequency strategy for the calculations, namely using different frequencies for the robot joint positions, velocities and accelarations. In the line of thought, this paper compares a multirate trajectory planning scheme in the cartesin space in contrast with the classical monofrequency claculation strategy.